2017
DOI: 10.15671/hjbc.2018.176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Licorice on Some Selected Properties of Ice Cream

Abstract: M eyan kökü teknolojik özelliklerinden, sağlık üzerine etkilerinden ve tadından dolayı gıda endüstrisinde kullanılmaktadır. Çalışmada meyan kökü kullanılarak farklı tatta yeni bir dondurma üretimi yapılmıştır. Karışıma %0.5 A, %1.0 B, %1.5 C, %2.0 D oranlarında meyan kökü ilavesi yapılarak elde edilen sonuçlar kontrol (meyan kökü içermeyen) örnek ile karşılaştırılmıştır. Meyan kökü dondurmanın renk ve genel kabul edilirliği gibi özellikerini geliştirdiği gözlemlenmiştir. Dondurma içerisine %1.5'e kadar meyan k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Studies have revealed that licorice possesses phenolic and terpenoid compounds that have the ability to be used to enhance oxidative stability as well as microbial safety of food products (Jiang et al, 2013). Hayo glu et al (2017) successfully attempted to develop ice cream with improved color, overrun and acceptability by incorporating 1.5% licorice in the formulation mixture of icecream. Similarly, Azami et al (2018) developed lower sugar functional drink with incorporation of cocoa powder: licorice extract powder ratio of 0.65:0.35 along with 5% sugar with good sensory acceptability and shelf life of 14 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that licorice possesses phenolic and terpenoid compounds that have the ability to be used to enhance oxidative stability as well as microbial safety of food products (Jiang et al, 2013). Hayo glu et al (2017) successfully attempted to develop ice cream with improved color, overrun and acceptability by incorporating 1.5% licorice in the formulation mixture of icecream. Similarly, Azami et al (2018) developed lower sugar functional drink with incorporation of cocoa powder: licorice extract powder ratio of 0.65:0.35 along with 5% sugar with good sensory acceptability and shelf life of 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…, 2013). Hayoğlu et al. (2017) successfully attempted to develop ice cream with improved color, overrun and acceptability by incorporating 1.5% licorice in the formulation mixture of ice-cream.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is consumed widely and also used in the treatment of diseases. Liquorice is evaluated as an enrichment material in different food products and a considerable ingredient of pharmaceutical and cosmetics (Hayoğlu et al, 2017;Tung et al, 2016;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%